Medical Visits From Birth to 6 Months Predict Child Maltreatment Diagnoses Up to Age 5. (December 2020) - Negriff, Sonya; DiGangi, Mercie J.; Sharp, Adam L.; Wu, Jun
Electronic health record data for pediatric members of Kaiser Permanente Southern California were used to identify key variables (ie, the number of emergency department visits and the number of providers) available in early infancy (0-6 months) placing children at higher risk of a maltreatment diagnosis in the first 5 years of life. The analytic sample included 96 462 children age 0 to 5 years born from January 1, 2009, to June 30, 2018. Poisson regression showed that children with ≥2 emergency department visits from birth to 6 months were at twice the risk of a maltreatment diagnosis before age 2 and 5 years compared with those children with no emergency department visits. Children with more continuity of primary care providers (0-5 providers) in the first 6 months of life were at lower risk of a maltreatment diagnosis at 2 years and 5 years than those children who saw multiple providers (6+). Information about medical utilization in early infancy may help physicians and other medical providers identify children at higher risk of maltreatment and prevent future incidents.